Evaluation of 3D Convolutional Neural Networks on Isolated Brazilian Sign Language Recognition - Lazzarotto, Lorenzo C.; Delucis, Marcelo M.; Barcelos, Pedro T.; Barros, Rodrigo C.; Kupssinskü, Lucas S. (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS); 2025: Anais da I Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul, 2025)
Isolated Sign Language Recognition plays a crucial role in advancing technologies that enhance accessibility for deaf individuals. In this work we investigate the performance of several 3D Convolutional Neural Networks on the task of ISLR in LIBRAS. Models were trained on the MINDS dataset and evaluated on an out-of-domain dataset, MALTA-LIBRAS. Experimental results indicate that while all models achieve high metrics on the training and validation data, they exhibit clear overfitting and fail to generalize effectively to unseen samples. These results highlight the challenges posed by limited data and data variability in ISLR for LIBRAS.